Molecular pairwise relatedness in autopolyploids: a simulation study considering linkage and many loci - Amadeu, Rodrigo Rampazo (2018)
Crops, such as sugarcane, potato, and several forages and berries, are autopolyploids. In plant breeding studies, a key subject is the pairwise relatedness between cultivars. This information can be incorporated in GWAS (genome-wide association) and GS (genomic selection) studies allowing powerful genetic analysis. Despite the autopolyploid importance in agriculture, they lack genetic studies considering ploidy level, and, therefore, polyssomic inheritance. Our objective in this work is: i) to investigate, through simulations, different molecular pairwise relatedness estimators; ii) to recommend which one is the best to be used in different scenarios regarding characteristic as number of loci, number of alleles, ploidy level, double-reduction, and inbreeding level. Our recommendations may guide autopolyploid breeding programs will be able to choose the best strategies and estimators based their reality.